Pemeriksaan Kesehatan Sebagai Upaya Deteksi Dini Penyakit Degeneratif di Kelurahan Sendangguwo - Dian NK; Syaifudin, Achmad; Komsiyah, Komsiyah; Dita Handayaningtyas, Ayu; Aldy Mandaty, Fhandy (PELITA NUSA TENGGARA, 2024)
Modern lifestyle can make most people lazy about doing physical activities such as sports. Apart from that, unbalanced diet, work demands, stress due to economic factors and exposure to pollution which can trigger free radicals will cause changes in the body. These factors unconsciously trigger the emergence of degenerative diseases. Lifestyle changes in food consumption are triggered by busy work and fast food promotions, but are not balanced by knowledge. Degenerative disease refers to a health condition characterized by the progressive destruction of tissue over time. This disease cannot be cured, it can only be managed to relieve and improve symptoms. Without people realizing, this degenerative disease occurs at the productive stage of life and people only get themselves checked after symptoms appear.